2022
DOI: 10.3389/fpsyg.2022.805740
|View full text |Cite
|
Sign up to set email alerts
|

Facing the Pandemic in Italy: Personality Profiles and Their Associations With Adaptive and Maladaptive Outcomes

Abstract: The negative impact of the COVID-19 pandemic on individuals’ psychosocial functioning was widely attested during the last year. However, the extent to which individual differences are associated with adaptive and maladaptive outcomes during quarantine in Italy remains largely unexplored. Using a person-oriented approach, the present study explored the association of personality profiles, based on three broad individual dispositions (i.e., positivity, irritability, and hostile rumination) and two self-efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 108 publications
(140 reference statements)
0
2
0
Order By: Relevance
“…In addition, previous research on personality types has shown that resilients seem to be generally well-adjusted in many respects (e.g., high life satisfaction and prosocial behavior, low levels of psychological distress, and few mental health problems), while both overcontrollers and undercontrollers seem to be less well-adjusted [8,42,43]. That is, resilients have the highest levels of resilience and the lowest levels of depression and anxiety among people with the three personality types.…”
Section: The Moderating Role Of Personality Typesmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, previous research on personality types has shown that resilients seem to be generally well-adjusted in many respects (e.g., high life satisfaction and prosocial behavior, low levels of psychological distress, and few mental health problems), while both overcontrollers and undercontrollers seem to be less well-adjusted [8,42,43]. That is, resilients have the highest levels of resilience and the lowest levels of depression and anxiety among people with the three personality types.…”
Section: The Moderating Role Of Personality Typesmentioning
confidence: 89%
“…Specifically, in terms of the direct effects, for undercontrollers, the relationships between COVID-19 information FOMO and depression and anxiety were strongest compared with the overcontrolled and adaptive groups. A possible explanation for this is that undercontrollers are at risk of the co-occurrence of internalizing and externalizing problems, while the adaptive group tends to have more prosocial behavior and less depression and anxiety [8,9,36,42]. Additionally, in terms of the indirect effects, only undercontrollers reported the indirect effects, while adaptive and overcontrolled groups reported no significant indirect effects.…”
Section: The Moderating Role Of Personality Typesmentioning
confidence: 99%